Enhancing recycled aggregate concrete with graphene quantum dots (GQDs): Refining wastes from construction demolitions and out-of-service railway sleepers - Anand Raj; Papassara Yamkasikorn; Atichon Kunawisarut; Chayut Ngamkhanong; Pitcha Jongvivatsakul; Lapyote Prasittisopin; Joongjai Panpranot; Sakdirat Kaewunruen (Developments in the Built Environment)
The disposal of construction and demolition waste (CDW) poses environmental challenges, whilst recycling CDW as coarse aggregate in concrete can help conserve natural resources. However, this often reduces strength and durability due to residues, increased porosity and the potential formation of ettringite. Recent studies have demonstrated the potential of Graphene Quantum Dots (GQDs) to enhance the performance of cement composites, particularly by improving strength and durability. This study examines the use of recycled coarse aggregates from CDW and dismantled railway sleepers, combined with GQDs, to enhance concrete performance. Never have such the investigations been delved into before elsewhere. Eighteen concrete mixes with 25–100 % recycled aggregates were tested, with and without 0.3 % GQDs (by weight of cement). Mechanical properties (compressive and flexural strength) and durability (water absorption, chloride penetration) were evaluated. Microstructural analysis via FESEM and EDS assessed concrete behaviour. Our new findings reveal that using recycled aggregates from random sources led to a reduction in both compressive and flexural strengths by 21.7 % and 18.2 % respectively, primarily due to increased porosity and ettringite formation. However, the addition of GQDs improved both compressive and flexural strengths by about 15 % by promoting the formation of calcium silicate hydrate (C-S-H) gel. Concrete incorporating recycled aggregates from used railway sleepers exhibited a smaller reduction in compressive strength, up to 11 %. The reduction in flexural strength was also lower, reaching up to 7 %. Microstructural analysis revealed that GQDs facilitated the formation of crystalline precipitates, thereby enhancing both the strength and durability of the concrete. Overall, our new insights suggest that incorporating GQDs into concrete with recycled aggregates not only helps conserve environmental resources but also enhances overall material performance.